2019
DOI: 10.1177/1747021819835148
|View full text |Cite
|
Sign up to set email alerts
|

Dollars do not determine detection: Monetary value associated with unexpected objects does not affect the likelihood of inattentional blindness

Abstract: Conscious perception often fails when an object appears unexpectedly and our attention is focused elsewhere (inattentional blindness). Although various factors have been identified that modulate the likelihood of this failure of awareness, it is not clear whether the monetary reward value associated with an object can affect whether or not this object is detected under conditions of inattention. We hypothesised that unexpectedly appearing objects that contain a feature linked to high value, as established via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Assuming that value was established via induction of hunger (see above), we did not find an effect of value of the unexpected object on the probability of its detection. This is consistent with Redlich et al, ( 2019 ) who found no significant effect of short-term learned monetary value on inattentional blindness. Nevertheless, our findings seem surprising as (A) previous research has shown a clear effect of hunger on attentional bias towards food stimuli (Morris & Dolan, 2001 ; Piech et al, 2010 ), (B) other studies have repeatedly shown that previously rewarded stimuli are preferentially processed and, thus, suggested that rewards are important in salience determination (Anderson, Laurent, & Yantis, 2011 ; Anderson & Yantis, 2012 ), and (C) noticing in an inattentional blindness paradigm has repeatedly been shown to be sensitive to other forms of value (attentional set: Most & Astur, 2005 ; Most et al, 2001 ; Koivisto & Revonuso, 2007 ; self-related stimuli: Mack & Rock, 1998 , or evolutionary predetermined value: New & German, 2015 ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Assuming that value was established via induction of hunger (see above), we did not find an effect of value of the unexpected object on the probability of its detection. This is consistent with Redlich et al, ( 2019 ) who found no significant effect of short-term learned monetary value on inattentional blindness. Nevertheless, our findings seem surprising as (A) previous research has shown a clear effect of hunger on attentional bias towards food stimuli (Morris & Dolan, 2001 ; Piech et al, 2010 ), (B) other studies have repeatedly shown that previously rewarded stimuli are preferentially processed and, thus, suggested that rewards are important in salience determination (Anderson, Laurent, & Yantis, 2011 ; Anderson & Yantis, 2012 ), and (C) noticing in an inattentional blindness paradigm has repeatedly been shown to be sensitive to other forms of value (attentional set: Most & Astur, 2005 ; Most et al, 2001 ; Koivisto & Revonuso, 2007 ; self-related stimuli: Mack & Rock, 1998 , or evolutionary predetermined value: New & German, 2015 ).…”
Section: Resultssupporting
confidence: 93%
“…The manipulation chosen in the present study might be potent enough to have an impact on a sensitive measure as reaction times (Piech et al, 2010;Tapper et al, 2010), but not on the binary measure of awareness. Similar, such measure differences have also been found for priming effects and monetary value (Redlich et al, 2019).…”
Section: Exploring Different Possible Explanations For the Null Findingssupporting
confidence: 77%
See 2 more Smart Citations
“…Similarly, when participants were given a task in which certain colors were associated with actual monetary rewards, the reward did not impact inattentional blindness (Redlich et al, 2019). In contrast, although military-trained CCTV operators missed seeing a woman setting down a suspicious package and then leaving in CCTV footage, researchers found that trained and novice operators were more likely to notice the woman setting down a package than they were to notice a woman in a pirate costume staying in frame for an equivalent period of time (Näsholm et al, 2014).…”
Section: Inattentional Blindness In Emotionally Arousing Scenariosmentioning
confidence: 99%